PENILAIAN PRESTASI KINERJA DENGAN METODE CHECKLIST DI ASTRA HONDA CABANG PT. HONDA SENAMA - Candrika Nugra Fitra; Muhammad Fajar Alam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The performance appraisal system is one of the most important parts and development and improvement of the quality of Human Resources (HR) in an organization, so its existence must always be evaluated so as not to deviate from its original purpose, namely to find out whether employees have met the standards previously set by the company or not during their work so far. Thus, the performance appraisal at Astra Honda Branch of PT Honda Senama is carried out using the checklist method, namely analyzing the company's environment on employee performance, observation, surveys and conducting questionnaires and analyzing employee assessment evaluations to be used as data in research. With high dedication and loyalty of employees in doing their work, and based on the skills and expertise they have, the efforts made will be more fruitful. This is where the company begins to appreciate their efforts and hard work by assessing the performance that has been carried out, performance itself comes from the word job performance or actual performance which means work achievement or actual achievement achieved by someone.